Stratigraphy and components of a funeral fardo of culture Chancay from Cerro Colorado, Huacho - Dalen Luna, Pieter van (2019)
During the excavations conducted on the Cerro Colorado site (Peruvian Central Coast), Pieter van Dalen discovered that some 40% of 1500 burials contained human remains wrapped in funerary bundles (fardos). The study of the associated material, along with radiocarbon dating, revealed that the cemetery was used by the society known today as the Chancay culture (ca. 1000 to 1572 AD). In this article we present the stratigraphy of one of the excavated funerary bundles. Its layout informs about the complexity of the funerary ritual during which it was made, as well as the general Chancay mortuary pattern.